Pengaruh Pupuk Urea terhadap Hasil Produksi Padi Desa Sumbersalak Kecamatan Ledokombo Kabupaten Jember - Moniaga, Moch. Feri; Purwandhini, Ari Septianingtyas (KUBIS, 2023)
Fertilizer is an important input for rice production, especially urea fertilizer is one of the most important fertilizers for agriculture, especially rice plants to increase rice production. The aim of the research was to determine the effect of the availability of urea fertilizer on rice production in Sumbersalak Village, Ledokombo District and to determine the effect of the increase in the price of urea fertilizer on rice production in Sumbersalak Village, Ledokombo District. The selection of the research location was carried out intentionally or purposive sampling. So that it determines 44 people as respondents who were taken deliberately and who are suitable as data sources. The analysis tool used is Multiple Regression. Based on the analysis, it is known that constant dependent variables such as availability (X1) and increases in fertilizer prices (X2) in decision making are known to influence rice production results.